The University of the Highlands and Islands project: A model for networked learning? - Adamson, Veronica; Plenderleith, Jane (Proceedings of the International Conference on Networked Learning, 2000)
The Highlands and Islands of Scotland are a remote and rugged expanse of land on the periphery of Britain and Europe. The region has Jong struggled against the adversity of isolation - geographic, economic and social - and has endured significant economic decline and depopulation. The area, from Shetland to the Mull of Kintyre, from the Western Isles to the foothills of the Cairngorms, comprises nearly twenty per cent of the land mass of Britain. It has less than one per cent of the UK population (fewer thar1 half a million inhabitants) and as such is one of the least densely populated areas of Europe. With the exception of the conurbation of Inverness. which is one of Europe’s fastest-growing towns and currently bidding for city status, most of the inhabitants live in small arid widely dispersed towns, villages and crofting communities. At the 1991 census there were ninety-three inhabited islands in archipelagos of Shetland and Orkney, and the Inner and Outer Hebrides.